2012
DOI: 10.1111/j.1365-2672.2012.05292.x
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence of Cronobacter spp. in retail foods

Abstract: Aims:  To study the occurrence of Cronobacter spp. in foods and to investigate the phenotypic properties of the strains isolated. Methods and Results:  A total of 53 strains of Cronobacter spp. isolated from 399 food samples were identified using conventional biochemical methods and MALDI‐TOF mass spectrometry. Foods of plant origin were the most frequently contaminated samples. No Cronobacter spp. were found in infant milk formula, wheat‐based infant food, pasteurized and raw cow milk, mincemeat, chicken, chi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
44
4
3

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(56 citation statements)
references
References 40 publications
5
44
4
3
Order By: Relevance
“…described Cronobacter strains recovered from foods that were resistant to cephalothin or ampicillin and susceptible to tetracycline. Hochel et al (2012) found that all Cronobacter isolates varied in their susceptibility to tetracycline. Muytjens & van der Ros-van de Repe (1986) examined Cronobacter susceptibility to 29 antimicrobial agents and found that Cronobacter were the most susceptible among other Enterobacteriaceae studied.…”
Section: Antibiotic Susceptibility and Resistancementioning
confidence: 99%
See 1 more Smart Citation
“…described Cronobacter strains recovered from foods that were resistant to cephalothin or ampicillin and susceptible to tetracycline. Hochel et al (2012) found that all Cronobacter isolates varied in their susceptibility to tetracycline. Muytjens & van der Ros-van de Repe (1986) examined Cronobacter susceptibility to 29 antimicrobial agents and found that Cronobacter were the most susceptible among other Enterobacteriaceae studied.…”
Section: Antibiotic Susceptibility and Resistancementioning
confidence: 99%
“…dried milk powder, dried meats, legumes, nuts, dried flours and spices) (Friedemann, 2007;Hochel et al, 2012) or drinking water (Lui et al, 2013). Although Cronobacter spp.…”
Section: Introductionmentioning
confidence: 99%
“…Despite the robustness of MLST, some researchers have continued to use biotyping to speciate their isolates [12, 13,14]. Presented here is a study investigating the reliability of the biotyping scheme for identifying the Cronobacter species.…”
mentioning
confidence: 99%
“…At a lower bacterial count (< 10 6 CFU/ml), background peaks became more prominent and affected spectrum matching. Although MALDI-TOF MS may become a popular identification method in food microbiology, there is little information on direct identification of bacteria in processed food products using MALDI-TOF MS (Angelakis et al, 2011;Böhme et al, 2011;Hochel et al, 2012). The separation of bacteria is conducted to harvest cells from complex food matrices that impede accurate detection (Benoit & Donahue 2003;Stevens & Jaykus, 2004).…”
Section: Resultsmentioning
confidence: 99%